INFLUENCE OF MADRASAH PRINCIPAL'S POLICY ON TEACHER PERFORMANCE AT FLAGSHIP MADRASAH IBTIDAIYAH JOMBANG - Anita Rachman; Mahmudi Mahmudi; Suwandi Suwandi (Fakultas Tarbiyah, Universitas Ibrahimy, 2025)
Teacher performance is a crucial element in education. Several issues related to teacher performance include the mismatch between academic disciplines and teaching areas, which hinders students' understanding, the qualification of teachers not meeting the required standards, teachers' welfare not being fulfilled, and a lack of understanding of the 2013 Curriculum (K13). According to the UNESCO Global Education Monitoring (GEM) Report 2016, Indonesia ranks 10th out of 14 developing countries in education, with the quality of teachers ranking 14th. This study aims to analyze teacher performance, madrasah head policies, and work motivation at MI Mujahidin Parimono Jombang. Using a quantitative approach with saturated sampling, the study involved teachers as respondents and utilized a questionnaire with 45 statements. The results showed that partially, the madrasah head's policy did not significantly affect teacher performance (sig. T = 0.916 > 0.05), while work motivation had a significant effect (sig. T = 0.041 < 0.05). Simultaneously, the madrasah head's policy and work motivation together significantly affected teacher performance (sig. F = 0.000 < 0.05).